Integrated linear reactor in transformer based on non-orthogonal decoupling method. (December 2020) - Xiang, Jinwen; Yang, Zhidong; Luo, Longfu; Tong, Nihan; Han, Chaowei; Yang, Shengjie
Abstract: The air-core reactor has the advantage of good linearity and low noise, however the problem of large space occupation. Power filter with the air-core reactor is indispensable with the widespread use of the power electronic devices in electrified transportation system and urban distribution system. It is hoped that the air-core reactor can be integrated in the transformer to reduce the space while the good performance of the power filter is kept. In this paper, a non-orthogonal decoupling (NOD) method is proposed, as well as a new design to integrate the linear reactor based on it. Further research including the structure of the integrated linear reactor (ILR) windings, the mechanism of the power decoupling among windings and the calculation of the inductance values are introduced. A 3-D finite-element simulation model is established which demonstrate the correctness of the analysis and provided an assistant approach of engineering design. Finally, the prototype system of the box-type distribution substation with integrated filter reactor and its experimental date are shown, the distribution transformer with integrated air-core reactors are confirmed to have excellent performance.